2013
DOI: 10.7314/apjcp.2013.14.11.6631
|View full text |Cite
|
Sign up to set email alerts
|

Networks of MicroRNAs and Genes in Retinoblastomas

Abstract: Through years of effort, researchers have made notable progress in gene and microRNA fields about retinoblastoma morbidity. However, experimentally validated data for genes, microRNAs (miRNAs) and transcription factors (TFs) can only be found in a scattered form, which makes it difficult to conclude the relationship between genes and retinoblastoma systematically. In this study, we regarded genes, miRNAs and TFs as elements in the regulatory network and focused on the relationship between pairs of examples. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…CTNNB1 exhibits a significant role in WT, while it is also involved in hepatoblastoma (18). Furthermore, hsa-let-7a is differentially expressed in WT, and is also overexpressed in retinoblastoma (19). The present study provides a novel perspective for biologists with regard to WT treatment.…”
Section: Discussionmentioning
confidence: 93%
“…CTNNB1 exhibits a significant role in WT, while it is also involved in hepatoblastoma (18). Furthermore, hsa-let-7a is differentially expressed in WT, and is also overexpressed in retinoblastoma (19). The present study provides a novel perspective for biologists with regard to WT treatment.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study indicated that MYCN is not only differentially expressed in HB, but also in Wilms' tumor (33). Furthermore, hsa-miR-373 is overexpressed in HB, and is also differentially expressed in retinoblastoma (34). Future studies should focus on the genes and miRNAs that are common in various types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…RB is a common intraocular malignant tumor in infants (Khaenam et al, 2012;Khan et al, 2013;Li et al, 2013;Maiti et al, 2013;Srivastava et al, 2013;Romus et al, 2013). Some children have been sick at birth and appear vision loss and even blindness in the early stage.…”
Section: Discussionmentioning
confidence: 99%